Taftisyul Kutub in Developing Student Skills in Junior High School - Nurmala, Ida; Acetylena, Sita; Husni, Muhammad (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
One of the frequent challenges Raudlatul Ulum Junio High School faces is the minimal attitude of care and compliance of students in doing the tasks received from teachers. As an educator, overcoming the existing challenges and implementing a decent solution to solve them is vital. The key is placed to hold a Taftisyul Kutub, where passing the Taftisyul Kutub examination is a prerequisite for following the written test. This research aims to examine in depth the implementation of the Taftisyul Pole and the skills that students generate from its performance. Qualitative research uses a participatory qualitative approach, where data collection techniques include observations, interviews, and documentation. Data is then analyzed based on data reduction components, data measurement, conclusion drawings, and verification to determine its validity using triangulation. The researchers' findings suggest that Taftisyul Polub is a strategy to reduce student disobedience. As for the skills acquired by students from the Taftisyul Kutub maintenance, that is, the development of collaborative skills, improved student understanding, the development of speaking and opinion skills, motivation, and student involvement.